THE SCOPE OF LITERARY IMAGINATION IN CLIMATE FICTION: A STUDY OF AMITAV GHOSH’S GUN ISLAND - Tasnim, Zakiyah (Journal of English Literature and Linguistic Studies, 2025)
Amitav Ghosh challenges conventional climate fiction writing in Gun Island by blending myths, folklore, and realism with his focus on climate change. This article explores how the novel uses literary imagination to present new perspectives on the climate crisis. It also examines the broader significance of climate fiction (cli-fi), the constraints of traditional realism, and the power of creative storytelling to inspire collective action.